Pendekatan Ahli Akademik Di Malaysia Dalam Menangani Amalan Bid’ah - Amran Abdul Halim; Ahmad Izzuddin Abu Bakar; Walid Mohd Said; Abdulloh Salaeh; Amiruddin Mohd Sobali (Universiti Sains Islam Malaysia, 2026)
Journal of Hadith Studies, Volume 10 Issue 2 Page (160–171)